A RESEARCH PROJECT ON SEXISM IN INDIAN LAWS- A JURISUDENTIAL ENQURY - Thampi, Gayathree P (PEOPLE: International Journal of Social Sciences, 2015)
The basic purpose of this project is to examine why law as it is does not confirm to any jurisprudential schools but rather, a fair amalgamation of it. Any given law, on close examination is apt to prove the same. So, easiest way to examine how inter-related law is with society, is to prove the very existence of this hesitation of Indian judiciary when dealing with sex and sexuality. The conformity of law to the wish of the general public and the resistance to change despite of the fact that change being inevitable to law, leads to a new theory of jurisprudence which has nothing new but everything unlike the past. – The unifying theory of jurisprudence, a perfect amalgamation of all existing jurisprudential theories